LAPAROSCOPIC MANAGEMENT OF A LARGE HYDATID CYST OF LIVER (CASE REPORT) - Padhy, Biren Prasad; Hota, P. K. (BALI MEDICAL JOURNAL; Vol 4 No 3 (2015), 2015)
Background: Hydatid disease in humans is endemic in sheep rearing regions. However, a worldwide distribution is encountered. This is a parasitic disease caused by Echinococcus granulossus, which is a cestode. Liver is the most affected organ. Surgery is the mainstay of treatment in hydatid cyst of liver. Since the popularization of laparoscopic surgery, hydatid cyst of liver is being treated laparoscopically in few of the centers. Spillage and anaphylactic reactions are the main pitfalls of laparoscopic management of the hydatid cyst of the liver. We present a case of hydatid cyst of liver, which was managed laparoscopically using Palanivelu Hydatid System (PHS) without any spillage or anaphylactic reaction.
Keywords: Liver hydatid, laparoscopy, Palanivelu hydatid system